1997
DOI: 10.1161/01.atv.17.12.3392
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Improve Systemic Arterial Compliance but Not Plasma Lipids in Menopausal and Perimenopausal Women

Abstract: The possibility that the heightened cardiovascular risk associated with the menopause, which is said to be ameliorated by soybeans, can be reduced with soy isoflavones was tested in 21 women. Although several were perimenopausal, all have been included. A placebo-controlled crossover trial tested the effects of 80-mg daily isoflavones (45 mg genistein) over 5- to 10-week periods. Systemic arterial compliance (arterial elasticity), which declined with age in this group, improved 26% (P < .001) compared with pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
189
5
16

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(225 citation statements)
references
References 21 publications
12
189
5
16
Order By: Relevance
“…The lack of differences in plasma lipid concentrations between soy and caseinate interventions suggests that the striking effect on vascular reactivity in soy-protein-fed women was not due to a reduction in cholesterol and/or triacylglycerol plasma concentration. These results are in accordance with a previous trial, carried out in menopausal and perimenopausal women, that detected a significant improvement in systemic arterial compliance, but not in plasma lipids when isoflavone pills (80 mg/day) were administered (Nestel et al, 1997). The soy protein effect on vascular reactivity might be explained by different mechanisms, such as the antioxidant effect of soy phytoestrogens, which could decrease the inactivation of nitric oxide, one of the most potent vasodilators released by the endothelium (Mombouli & Vanhoutte, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of differences in plasma lipid concentrations between soy and caseinate interventions suggests that the striking effect on vascular reactivity in soy-protein-fed women was not due to a reduction in cholesterol and/or triacylglycerol plasma concentration. These results are in accordance with a previous trial, carried out in menopausal and perimenopausal women, that detected a significant improvement in systemic arterial compliance, but not in plasma lipids when isoflavone pills (80 mg/day) were administered (Nestel et al, 1997). The soy protein effect on vascular reactivity might be explained by different mechanisms, such as the antioxidant effect of soy phytoestrogens, which could decrease the inactivation of nitric oxide, one of the most potent vasodilators released by the endothelium (Mombouli & Vanhoutte, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…The recovery during the intervention with F of 18.9 mg/day or just under 25% of the ingested amount is similar to amounts that we have reported (Nestel et al, 1997;Tsunoda et al, 2002). Nonurinary routes of excretion and failure to measure minor metabolites (only equol and O-desmethylangloensin were measured) contribute to underestimation.…”
Section: Discussionsupporting
confidence: 78%
“…Two issues arise therefore: the reasons for the different gender response and for the greater benefit from biochanin, the precursor of genistein. The present findings of a differential response between men and women and between the responses to biochanin and formononetin may help explain the failure by ourselves (Nestel et al, 1997(Nestel et al, , 1999 and others (Hodgson et al, 1998;Howes et al, 2000;Simons et al, 2000) to demonstrate an effect on plasma LDL-C with isolated isoflavones. In each of the previous studies, the isoflavones contained a mixture of B and F that would have diluted any effect attributable to B alone.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…There is limited evidence in humans that bone metabolism is affected favorably by the isoflavone derivative ipriflavone [21] and by soy isoflavones [22,23]. Studies in humans have shown that phytoestrogens decrease plasma lipids [24,25], LDL oxidation [26,27], arterial compliance [28] and endothelial cell damage [26]. These observations are strengthened by experimental data in atherosclerotic non-human primates, indicating that cardiovascular risk factors [29,30], coronary artery atherosclerosis [31], coronary vascular reactivity [32] and aortic cholesteryl ester content [30] are influenced favorably.…”
Section: Introductionmentioning
confidence: 99%